Frankincense: A neuronutrient to approach Parkinson’s disease treatment - Calabrese Vittorio; Osakabe Naomi; Khan Foziya; Wenzel Uwe; Modafferi Sergio; Nicolosi Lidia; Fritsch Tilman; Jacob Ursula M.; Abdelhameed Ali S.; Rashan Luay (Open Medicine, 2024)
Parkinson’s disease (PD), characterized by tremor, slowness of movement, stiffness, and poor balance, is due to a significant loss of dopaminergic neurons in the substantia nigra pars compacta and dopaminergic nerve terminals in the striatum with deficit of dopamine. To date the mechanisms sustaining PD pathogenesis are under investigation; however, a solid body of experimental evidence involves neuroinflammation, mitochondrial dysfunction, oxidative stress, and apoptotic cell death as the crucial factors operating in the pathogenesis of PD. Nutrition is known to modulate neuroinflammatory processes implicated in the pathogenesis and progression of this neurodegenerative disorder. Consistent with this notion, the Burseraceae family, which includes the genera Boswellia and Commiphora, are attracting emerging interest in the treatment of a wide range of pathological conditions, including neuroinflammation and cognitive decline. Bioactive components present in these species have been shown to improve cognitive function and to protect neurons from degeneration in in vitro, animal, as well as clinical research. These effects are mediated through the anti-inflammatory, antiamyloidogenic, anti-apoptotic, and antioxidative properties of bioactive components. Although many studies have exploited possible therapeutic approaches, data from human studies are lacking and their neuroprotective potential makes them a promising option for preventing and treating major neurodegenerative disorders.